The effect of bosentan on the pharmacokinetics of digoxin in healthy male subjects - Weber, Cornelia (Blackwell Science Inc, 1999)
AIMS: To investigate the effect of multiple oral dose treatment with the endothelin receptor antagonist bosentan on the pharmacokinetics of digoxin in healthy subjects. METHODS: This was an open-label, randomized, two-way crossover study in 18 evaluable young male subjects. They received, on two occasions which were separated by at least 2 weeks washout period, 0.375 mg digoxin once daily for 13 days following a loading dose of 0.375 mg given twice on the day before the once daily dosing regimen started. On one occasion treatment with 500 mg bosentan twice daily was started on the eighth day of digoxin treatment and continued for 1 week. Serum concentrations of digoxin were determined up to 24 h postdose on day 8 (first day of bosentan treatment) and day 14 (last day of bosentan treatment) of the digoxin treatment period. Plasma concentrations of bosentan were measured at two time points after the first bosentan dose and up to 12 h after the last morning dose of bosentan. Safety was assessed by adverse events, clinical laboratory tests, blood pressure and pulse rate measurements and ECG recordings. RESULTS: Steady-state of digoxin was always achieved after 7 days of treatment. Serum concentrations of digoxin were within the usual therapeutic range. Average steady-state C(max) and C(tr) were 2–2.1 μg l(−1) and 0.65–0.69 μg l(−1), respectively, when given alone. Bosentan did not lead to statistically significant changes in C(max) and C(tr) of digoxin. AUC (0,24h) of digoxin, however, was slightly reduced after 1 week of treatment with bosentan. The reduction was 12% on average with a narrow 95% confidence interval of 0-23%. Bosentan pharmacokinetic parameters after 1 week of treatment were as expected with a mean C(max) of 3260 μg l(−1) and a mean AUC (0,12h) of 12600 μg l(−1) h. CONCLUSIONS: Treatment with bosentan 500 mg twice daily for 1 week did not show clinically relevant effects on the pharmacokinetics of digoxin in healthy human subjects